Adsorption removal of thiocyanate from aqueous solution by using reusable AgCl-loaded carbon - Guobao Chen; Aikun Sun; Pengcheng Ma; Qifei Sun (Desalination and Water Treatment)
A novel adsorbent with silver chloride-loaded activated carbon (AgCl/C) was synthesized by a simple one-step process. The morphological properties and the constitutive components of the adsorbent thus prepared were characterized. The adsorption experiments for the removal of thiocyanate with AgCl/C from aqueous solution were carried out. The removal effect of thiocyanate was analyzed and compared with the different materials. The results show that the removal efficiency for the AgCl/C adsorbent can reach more than 98% in the temperature range of 20–30 ℃ and pH range of 2–12. The adsorptive mechanism of AgCl/C to remove thiocyanate was also discussed. The adsorbent can be recycled using sodium hypochlorite solution, and the highest removal efficiency of thiocyanate using the regenerated AgCl/C can still reach 94.5%.